تحديد الحدود البحرية بين الدول المتقابلة والمتلاصقة - احمد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تتكون الدولة من ثلاثة عناصر أساسية وهي: العنصر البشري (الشعب) والعنصر المادي (الإقليم) والعنصر التنظيمي (السلطة)، وإقليم كل دولة يتكون من الإقليم البري والإقليم الجوي يضاف إليهما الإقليم البحري إذا كانت دولة ساحلية. والإقليم البحري لم يعد مقتصراً على المياه الداخلية والبحر الإقليمي إنما امتد ليشمل مجالات بحرية جديدة لم تكن تعتبر كذلك قبل توقيع اتفاقية الأمم المتحدة لقانون البحار لعام 1982. كالمنطقة الاقتصادية والجرف القاري اللذين يمتدان حتى مسافة مائتي ميل من خطوط الأساس. وحتى الوقت الراهن معظم الدول لم تحدد حدودها البحرية بشكل كاف بل إن خلق مجالات بحرية جديدة في الاتفاقية اقتضى من جميع الدول إعادة التحديد. ونظراً لحساسية موضوع التحديد لتعلقه بالمصالح الحيوية والقومية العليا للدولة فقد دأبت مؤتمرات قانون البحار المتعاقبة إلى وضع وتثبيت قواعد دولية تحكم تحديد المجالات البحرية المختلفة لما لها من دور في حفظ السلم والأمن العالمي. وهذا ما فعلته الاتفاقية الجديدة التي تعتبر بحق (دستوراً للبحار) لما أرسته من قواعد ومبادئ في كل ما يتعلق بالبحار. سنسلط الضوء على الوسائل القانونية التي وظيفتها الاتفاقية لتحديد الحدود البحرية وكذلك على الاتفاقيات الدولية الأخرى،و على وأحكام القضاء الدولي لتحديد الحدود البحرية بين الدول المتقابلة والمتلاصقة. The state consists of three main elements: The human element (people), the physical component (the region) and regulatory element (authority). The territory of state consists of the provincial land air region and maritime territory if thestate and the maritime territory is no longer specified with inlandwater but new dimentions are included which were not known before the signing the agreement of the UN convention on the law of sea in 1982 such as the exclusive economic zone and the continental shelf which extended about 200 mile from the base lines. Until the moment, most countries did not delimite their marine border completely, but creating new mrine areas in the convention requires to playback’ delimitation. According to sensitivity of the case of delimitation which related to the vital and national interests of the state, the successive conferences tried to put permanent international rules which control the identification of different marine fields which had a great influence on keeping global peace and security. What the new agreement did which was the right constitution of the sea because it laid down all the rules and principles relating to the sea. We will shed light on legal methods which established by the agreement of delimitation of the marine borders in various marine fields among the opposite and a djiaeant states in the addition to other international conventions and resolution of international justice.